2021
DOI: 10.1016/j.jpsychores.2021.110516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety, and insomnia symptoms among patients with COVID-19: A meta-analysis of quality effects model

Abstract: Background Evidence from previous virus epidemics has shown that infected patients are at risk for developing psychiatric and mental health disorders, such as depression, anxiety, and insomnia. Hence, to collect high-quality data on the impact of COVID-19 pandemic on the prevalence of depression, anxiety, and insomnia symptoms among patients infected with SARS-CoV-2 should be the immediate priority. Methods A comprehensive search of Medline, Embase, Web of Science, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 49 publications
5
62
1
2
Order By: Relevance
“…For example, a meta-analysis of 44 studies conducted in 13 countries revealed a 35.7% prevalence rate of sleep problems across studies conducted in the general population, although no standard criteria or measures were used across studies to define sleep problems. In another meta-analysis of 22 studies, rates of depression and anxiety (38% for each) and of insomnia (48%) were even higher than the current one, although the definitions of each conditions were not the same as in the present study [ 6 ]. Another meta-analysis of studies conducted with health-care workers [ 9 ] found pooled prevalence of 38.9% for insomnia, 23.2% for anxiety, and 22.8% for depression.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…For example, a meta-analysis of 44 studies conducted in 13 countries revealed a 35.7% prevalence rate of sleep problems across studies conducted in the general population, although no standard criteria or measures were used across studies to define sleep problems. In another meta-analysis of 22 studies, rates of depression and anxiety (38% for each) and of insomnia (48%) were even higher than the current one, although the definitions of each conditions were not the same as in the present study [ 6 ]. Another meta-analysis of studies conducted with health-care workers [ 9 ] found pooled prevalence of 38.9% for insomnia, 23.2% for anxiety, and 22.8% for depression.…”
Section: Discussioncontrasting
confidence: 66%
“…Surveys conducted in several countries since the beginning of the pandemic, as well as meta-analyses [ [3] , [4] , [5] , [6] ], have reported very high and variable rates of insomnia (20–35%), anxiety (20–45%), and depression (25–50%) in the general population [ 7 , 8 ], with rates even higher among health-care workers [ [9] , [10] , [11] , [12] ] and patients with COVID-19 [ 6 ]. Such estimates clearly exceed base rates reported in most epidemiological studies conducted under normal circumstances (ie, pre-pandemic) and using similar criteria [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pandemic has been associated with an increased prevalence of psychological health issues, in addition to the more obvious physical health consequences [ 3 , 4 ]. The disease affects different aspects of people's lives and different communities in the society, including health care workers (HCWs) [ 5 , 6 ]. HCWs, due to frequent contact with COVID-19 patients, are at high risk of infection transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis of Liu et al [54] documented that depression, anxiety and insomnia symptoms were highly prevalent in the COVID-19 patients, even higher than the general population affected by the outbreak. In this meta-analysis, insomnia symptoms and being a female come to the forefront.…”
Section: Depression Anxiety and Sleep Problemsmentioning
confidence: 99%